2016
DOI: 10.1097/iio.0000000000000112
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Haze Following Refractive Surgery

Abstract: Corneal transparency is essential to visual clarity. The anatomy of the cornea is specifically designed to neither scatter nor absorb light. The spacing and parallel nature of collagen fibers, relative lack of cellularity, and transparent extracellular matrix all contribute to corneal clarity. Surface ablative forms of refractive surgery have been well known to be associated with postoperative corneal haze formation, which is initiated by the complex corneal healing response. 1,2 Haze formation can prolong tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Fibrosis is the leading cause of corneal blindness and can potentially be treated by targeted gene therapy [4,7,10]. Following corneal injury, TGFβ drives pro-fibrotic responses by enhancing ECM gene expression, and is responsible for the conversion of fibroblasts into myofibroblasts [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibrosis is the leading cause of corneal blindness and can potentially be treated by targeted gene therapy [4,7,10]. Following corneal injury, TGFβ drives pro-fibrotic responses by enhancing ECM gene expression, and is responsible for the conversion of fibroblasts into myofibroblasts [34].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal scarring is the third leading cause of blindness globally, affecting 1.3 million Americans each year [2,3]. Currently, no effective topical treatments exist that cure corneal scarring and the use of intra-operative drugs such as MMC (Mitomycin C) for prevention of corneal haze can be problematic [4]. Hence, corneal transplantation remains the gold standard for treatment of corneal blindness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofibroblasts produce disorganized collagen, causing the appearance of corneal haze and leading to increased light scattering and decreased visual acuity 1. The mainstay in prevention of visually significant corneal haze involves decreasing the corneal inflammatory response with anti-inflammatory medications such as topical corticosteroids or other immunomodulatory medications 2. Previous studies have demonstrated topical corticosteroids to be beneficial in modulating post-PRK corneal inflammatory response, as well as reducing regression 3,4.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure causes more postoperative pain, delayed epithelial healing, and stromal haze, when compared to Laser in situ keratomileusis (LASIK). [ 1 2 3 ] However, because of the flap-related complications of LASIK, surface ablation techniques are preferred by many surgeons. [ 4 ] Previously, in surface ablation, the epithelium was removed manually (PRK), before the excimer laser application.…”
mentioning
confidence: 99%